Pengaruh Lingkungan Kerja Fisik Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Alsun Suksesindo Jakarta Utara - Padli Maulana Wahab; Dewi Sartika (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to determine the partial and simultaneous effects of the physical work environment and work discipline on employee performance at PT. Alsun Suksesindo, North Jakarta. The method used in this research is quantitative. The sampling technique used saturated sampling, resulting in a sample of 71 respondents. Data analysis techniques included validity testing, reliability testing, classical assumption testing, linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results indicate that the physical work environment variable has a simple linear regression equation of Y = 13.583 + 0.701X1. The correlation coefficient value is 0.720, which falls into the strong category. The coefficient of determination shows that variable X1 influences employee performance by 51.9%. The significance value is 0.000 < 0.05, and the calculated t-count is 8.628 > t-table 1.995, leading to the conclusion that the physical work environment has a significant effect on employee performance. The work discipline variable has a simple linear regression equation of Y = 8.270 + 0.806X2. The correlation coefficient value of r = 0.905 is categorized as very strong. The coefficient of determination shows that variable X2 influences employee performance by 81.9%. The significance value is 0.000 < 0.05, and the calculated t-count is 17.663 > t-table 1.995, indicating that work discipline has a significant effect on employee performance. The results for the physical work environment and work discipline variables have a multiple linear regression equation of Y = 6.788 + 0.121X1 + 0.725X2. The correlation coefficient value of r = 0.909 is categorized as very strong. The coefficient of determination indicates that variables X1 and X2 jointly influence employee performance by 82.6%. The F-test results show that F-count 161.426 > F-table 3.132 with a significance value of 0.000 < 0.05 This means that simultaneously, of the physical work environment and work discipline have a significant effect on employee performance